The relationship between disordered pursuit and vestibulo-ocular reflex suppression - Chambers, Br (1983)
The performance of the smooth pursuit reflex and the ability to suppress the vestibulo-ocular reflex were assessed in 10 normal subjects and in patients with a variety of diseases of the central nervous system. Pursuit was measured as the maximum velocity of slow phase eye movement in response to a laser target moving sinusoidally at various frequencies up to 1 Hz and with amplitudes stepped up to 35° peak. Suppression of the vestibulo-ocular reflex was assessed with subjects seated in a Barany chair rotating sinusoidally in yaw at matching frequencies. The breakpoint of vestibulo-ocular reflex supression was defined as the peak velocity of oscillation at which nystagmus appeared on electro-oculographic recording as determined by the method of ascending and descending thresholds. For normal subjects, at all frequencies, the breakpoint of suppression corresponded closely with the peak velocity of pursuit at the corresponding frequency of target oscillation. In some patients pursuit and suppression were comparably impaired. In others either pursuit or suppression could be selectively impaired with the other function left intact. The results demonstrate that the mechanisms of pursuit and visual suppression of the vestibulo-ocular reflex have similar dynamics and share a common pathway at least to the level of the cerebellum. Thereafter, there is presumably an anatomical and functional dissociation of the signals mediating the two functions. The key area involved appears to be the flocculus for lesions of this structure alone cause impairment of both functions. The findings also indicate that the appropriate way to test smooth pursuit in relationship to suppression is to increase the amplitude of target oscillation until the peak slow eye movement velocity is determined for each frequency. The finding that increasing excursion increases maximum pursuit velocity supports the view that pursuit has an acceleration limit which is more critical in determining performance than velocity limitations. The results establish the assessment of vestibulo-ocular reflex suppression as a powerful test of the integrity of CNS function independent of its previous association with disordered pursuit.